Insulin-like growth factor receptor cooperates with integrin alpha v beta 5 to promote tumor cell dissemination in vivo. - Brooks, P C (1997)
Tumor cell interactions with adhesion proteins and growth factors likely contribute to the metastatic cascade. Evidence is provided that insulin or insulin-like growth factor-mediated signals cooperate with the commonly expressed integrin alpha v beta 5 to promote spontaneous pulmonary metastasis of multiple tumor cell types in both the chick embryo and severe combined immune deficiency mouse/human chimeric models. Expression of alpha v beta 5 in tumor cells promoted their adhesion to vitronectin in vitro. However, cell motility required cytokine stimulation, which caused redistribution of alpha-actinin to membrane-adhesive sites containing alpha v beta 5. Significantly, ligation of alpha v beta 5 and cytokine receptors were both required for spontaneous pulmonary metastasis of multiple tumor types even though it was not necessary for primary tumor growth. Thus, tumor cell metastasis can be regulated by a functional cooperation between cytokine signaling events and the adhesion receptor alpha v beta 5 in a manner independent of tumor cell growth. These findings provide evidence that integrin ligation, in conjunction with cytokine activation, plays an important role in the dissemination of malignant tumor cells.